Yield, quality and water use efficiency of processing tomatoes produced under different irrigation regimes in Mediterranean environment - Lovelli, Stella; Potenza, Giovanna; Castronuovo, Donato; Perniola, Michele; Candido, Vincenzo (Italian Journal of Agronomy, 2017)
Marketable yield is the main objective in tomato production, but fair values for quality parameters are also becoming very important. A research project was undertaken for two years to assess the impact of water-saving techniques on yield, fruit quality and water use efficiency (WUE) of processing tomato (cv. Pullrex) in the Mediterranean environment. Additionally, to better understand how irrigation may affect tomato traits, different statistical techniques were applied to the results. Total yield was reduced by 37% on average in both years when half of the crop evapotranspiration (ET) was restored, and maximum marketable tomato yield was obtained under irrigation when 100% of the crop ET was restored. Irrigation cut at tomato veraison (irrigation cutback treatment) did not affect the yield, enhanced fruit quality and maximised WUE, thus contributing to water saving. Through the application of irrigation cutback toward the end of the tomato cycle, there is a possibility to improve tomato quality and, at the same time, save irrigation water. Principal component analysis confirmed that the cutback of irrigation was well correlated with tomato quality.